Secure Software Defined Vehicular Network (SDVN) - Umesh K Raut, Dr. Manoj K Rawat (International Journal of Advanced Science and Technology, 2020)
For Intelligent Transportation Services (ITS), new protocols and architecture are continuously being developed by researchers around the globe. Thus, to ensure the safety of drivers many countries are now adopting and investing a lot on vehicular network (VN). On the other perspective, there are many issues like integrity, Security and so on, related to this field that must be resolved before VN technology is practically adopted. In the case of no or low-security, several attacks can occur that may affect the efficiency and the reliability of the system. The search for better networking paradigms has fostered the emergence of Software Defined Networking (SDN), which allows the decoupling of the data plane from the control plane and to configure the network dynamically. SDN provides network operators with significant visibility and granularity of their networks leading to more flexibility in programming these networks. To make VN systems more efficient software defined networking (SDN) technology is introduced with VN. Typically, with every new technology paradigm, the security concerns represent a serious challenge. In this paper, we provide a comprehensive SDN security review including the different vulnerabilities and attacks that SDN suffers from. The objective is to entice the SDN community to address such issues inherently and not as an afterthought.